re:print : Ronny Delrue, Honoré d'O, Kendell Geers, Vincent Geyskens, Tina Gillen, Pieter Vermeersch. - Pas, Johan; Van Rillaer, Jos; Leemans, Koen; Mels, Mieke; Frans Masereel Centrum, Kasterlee (Mechelen : Cultuurcentrum Mechelen, 2009)
Delrue, Ronny ; d'O, Honoré ; Geers, Kendell ; Geyskens, Vincent ; Gillen, Tina ; Vermeersch, Pieter
uitgave bevat 7 aparte boeken: een reader en een overzicht per kunstenaar
re:print, Frans Masereel Centrum, Kasterlee, najaar 2009
kunstcatalogus